Immune-awakening Saccharomyces-inspired nanocarrier for oral target delivery to lymph and tumors - Yuling Mao; Xiudan Wang; Caishun Chen; Qinfu Zhao; Yanfeng Liu; Jinghai Zhang; Siling Wang (Elsevier, 2022)
Utilization of the intestinal lymphatic pathway will allow extraordinary gains in lymph and tumors cascade-targeted delivery of oral drugs and awakening the innate/adaptive immunity of the body and the lesion microenvironment, in addition to improving oral bioavailability relative to other means of delivery of oral drugs. Here, inspired by the specific invasion route of intestinal microorganisms, we pioneered an immune-awakening Saccharomyces-inspired mesoporous silicon nanoparticle (yMSN) for the ingenious cascade-targeted delivery of therapeutic cancer vaccines and antitumor drugs to lymph and tumors via the intestinal lymphatic pathway. Encouragingly, yMSN high-loaded tumor-specific antigens (OVA, 11.9%) and anti-tumor drugs (Len, 28.6%) with high stability, namely Len/OVA/yMSN, efficiently co-delivered OVA and Len to their desired target sites. Moreover, yMSN concomitantly awakened the innate antitumor immunity of dendritic cells and macrophages, strengthening vaccine-induced adaptive immune responses and reversing macrophage-associated immunosuppression in the tumor microenvironment. Surprisingly, Len/OVA/yMSN treatment resulted in excellent synergistic antitumor efficacy and long-term antitumor memory in OVA-Hepa1-6-bearing mice. This high-performance nanocarrier provides a novel approach for lesion-targeting delivery of oral drugs accompanied with awakening of the innate/adaptive immunity of the lesion environment, and also represents a novel path for the oral delivery of diverse therapeutic agents targeting other lymph-mediated diseases.